PENGARUH KREDIBILITAS BEAUTY INFLUENCER TERHADAP SIKAP KONSUMEN PRODUK KECANTIKAN (Survei Pada Followers Instagram Abel Cantika) - Salwa Safyra (2023)
The development of beauty trends, making the figure of beauty influencers who have high credibility is needed today. Based on the ZAP Beauty Index 2023 survey, 78% of Indonesian women choose local influencers in influencing women to choose beauty products. The purpose of this study is to find out how much influence the credibility of beauty influencers has on the attitude of beauty product consumers. The theory used is the theory of source credibility. This study uses a quantitative approach. The sample in this study was Abel Cantika's (@abellyc) Instagram followers, totalling 100 respondents, aged 18-24 years, and had an interest in beauty products. The method used in this study is a survey method by distributing questionnaires online using Google Forms. The results of the hypothesis test or T test stated that Ho was rejected and Ha was accepted, which means that there is an influence of Beauty Influencer Credibility (variable X) on Consumer Attitudes (variable Y). This is obtained from the results of the t count > t table, namely 7.838 > 1.661. Based on the calculation of the coefficient of determination test, it shows that 38.5% of the Consumer Attitude (variable Y) is influenced by the Beauty Influencer Credibility (variable X). Meanwhile, 61.4% is determined by other factors, such as product safety, product composition, product price, and others. This study supports the theory of source credibility. This study supports the theory of source credibility. This is evidenced by the research results which are supported by the positive responses of respondents, namely Abel Cantika as a beauty influencer has high credibility so she can influence the attitudes of her followers.